Association of Clinical Features of Colorectal Cancer with Circulating Tumor Cells and Systemic Inflammatory Markers. (21st April 2022) - Xing, Yasi; Qin, Fangyuan; Zhai, Yaping; Yang, Jingwen; Yan, Yiyang; Li, Dan; Zhang, Han; Hu, Renwang; Xu, Xianjing; Cao, Xuanchao; Huang, Gairong; Liu, Xiang
Abstract : Background. Circulating tumor cells (CTCs) in peripheral blood have been shown to reflect the prognosis of patients with colorectal cancer, and epithelial and mesenchymal markers further predict the likelihood of cancer dissemination. This study was conducted to identify possible association of clinical features of colorectal cancer with CTC counts, their subtypes, and systemic inflammatory markers. Methods. Blood samples of 316 colorectal cancer patients were used for CTC detection and subtyping with EpCAM, CK8/18/19, vimentin, and twist as biomarkers. The neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, C-reactive protein/albumin ratio, lymphocyte/monocyte ratio, and systemic immune-inflammation index (SII) were also measured. The relationship between clinical data and these markers or parameters was analyzed. Results. Total CTC counts were correlated with whether there was lymph node involvement but was not correlated with TNM staging. There was a difference in mesenchymal CTCs between patients with and without lymph node involvement (P < 0.05 ). Also, more patients with metastasis tested positive for mesenchymal CTCs (P < 0.05 ). Of the systemic inflammatory markers, platelet/lymphocyte ratio was positively correlated with CTC counts (P < 0.01 ), and lymphocyte/monocyte ratio was negatively correlated with CTC counts (P < 0.05 ). Conclusions. Colorectal cancer patients with the mesenchymal markers on their CTCs are more likely to have lymph node involvement or distant metastasis than those without these markers.